2008
DOI: 10.1089/hum.2008.107
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Leber Congenital Amaurosis Due toRPE65Mutations by Ocular Subretinal Injection of Adeno-Associated Virus Gene Vector: Short-Term Results of a Phase I Trial

Abstract: Leber congenital amaurosis (LCA) is a group of autosomal recessive blinding retinal diseases that are incurable. One molecular form is caused by mutations in the RPE65 (retinal pigment epithelium-specific 65-kDa) gene. A recombinant adeno-associated virus serotype 2 (rAAV2) vector, altered to carry the human RPE65 gene (rAAV2-CB SB -hRPE65), restored vision in animal models with RPE65 deficiency. A clinical trial was designed to assess the safety of rAAV2-CB SB -hRPE65 in subjects with RPE65-LCA. Three young a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
382
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 845 publications
(385 citation statements)
references
References 50 publications
0
382
0
3
Order By: Relevance
“…More recently, nonintegrating adenoviral vectors (Stadtfeld et al, 2008) and plasmid DNAs (Okita et al, 2008) have been used to deliver Klf4, Oct3/4, and Sox2 genes to fibroblasts, but the efficiency of reprogramming is low, ranging between 0.01 and 0.1%. Thus, we believe that further development of alternative vector systems, such as AAV, needs to be pursued for their potential ability to infect MSCs and fibroblasts, as well as to generate iPS cells at high efficiency, given the proven safety of AAV vectors in several clinical trials (Bainbridge et al, 2008;Hauswirth et al, 2008;Maguire et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, nonintegrating adenoviral vectors (Stadtfeld et al, 2008) and plasmid DNAs (Okita et al, 2008) have been used to deliver Klf4, Oct3/4, and Sox2 genes to fibroblasts, but the efficiency of reprogramming is low, ranging between 0.01 and 0.1%. Thus, we believe that further development of alternative vector systems, such as AAV, needs to be pursued for their potential ability to infect MSCs and fibroblasts, as well as to generate iPS cells at high efficiency, given the proven safety of AAV vectors in several clinical trials (Bainbridge et al, 2008;Hauswirth et al, 2008;Maguire et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant retro-and lentiviral vectors can also undergo random integration into host chromosome, thereby elevating the risk of insertional mutagenesis (Cockrell and Kafri, 2007;Nair, 2008). Thus, development of alternative vector systems, such as adeno-associated virus (AAV), needs to be pursued, given the proven safety of AAV vectors in several Phase I/II clinical trials (Bainbridge et al, 2008;Cideciyan et al, 2008;Hauswirth et al, 2008;Maguire et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The hope is that the working gene will repair malfunctioning cells and keep them alive, preserving and even improving vision. Trials by three different groups [1][2][3][4] have shown not only that the procedure is safe, but also that it boosts vision in most participants -and that most improvements seem to be maintained for up to seven years. The biotechnology company Spark Therapeutics in Philadelphia, Pennsylvania, is now testing gene therapy for LCA2 in an advanced trial, and it hopes to file for regulatory approval in the United States as early as 2016.…”
Section: S M a L L S T E P Smentioning
confidence: 99%
“…With the progress of molecular genetics increasingly more detailed, genotypes of these conditions are being identified, better predictive testing is becoming available and a more accurate estimation of future vision is possible (Pradhan et al 2009). This has been followed by the start of gene therapy trials in animal models of human retinal degeneration and the early results of gene therapy for RPE65-mediated disease are encouraging (Simonelli et al 2010;Le Meur et al 2007;Hauswirth et al 2008;Bainbridge et al 2008). Stem cell therapy has also shown promise in animal models and clinical trials of stem cell therapy for inherited retinal disease are imminent (Tucker et al 2011;Wong et al 2011).…”
Section: Introductionmentioning
confidence: 99%